Labora in Christian Theology: Exploring Its Significance in Relation to Blessings and Salvation - Naomi Sampe; Darius Darius (Sekolah Tinggi Theologia Jaffray, 2023)
The purpose of this research is to explore the meaning of work in Christian theology, particularly in relation to God's plan and providence, forgiveness, and salvation. The method employed in this study is a literature review of Bible verses, theological texts, and scholarly articles on the topic of work ethics in Christianity. The findings of this research indicate that work is not only a blessing and a privilege for humans as God's stewards on Earth but also a part of God's plan for salvation and forgiveness. The Holy Spirit utilizes human work in accordance with the purpose of salvation, thereby making work an essential ritual in life. All humans are created by God and adopted as children in Jesus Christ, and God works for the good of those who love Him. This research contributes to the understanding of the theological significance of work in the lives of Christians and its role in the existential faith as the people of God.